High arsenic contamination and presence of other trace metals in drinking water of Kushtia district, Bangladesh. (15th July 2019) - Huq, Md. Enamul; Fahad, Shah; Shao, Zhenfeng; Sarven, Most. Sinthia; Al-Huqail, Asma A.; Siddiqui, Manzer H.; Habib ur Rahman, Muhammad; Khan, Imtiaz Ali; Alam, Mukhtar; Saeed, Muhammad; Rauf, Abdur; Basir, Abdul; et al.
Abstract: Drinking water with excessive concentration levels of arsenic (As) is a great threat to human health. A hydrochemical approach was employed in 50 drinking water samples (collected from Kushtia district, Bangladesh) to examine the occurrence of geogenic As and the presence of trace metals (TMs), as well as the factors controlling As release in aquifers. The results reveal that the drinking water of shallow aquifers is highly contaminated by As (6.05–590.7 μg/L); 82% of samples were found to exceed the WHO recommended limit (10 μg/L) for potable water, but the concentrations of Si, B, Mn, Sr, Se, Ba, Fe, Cd, Pb, F, U, Ni, Li, and Cr were within safe limits. The Ca-HCO3 -type drinking water was identified as having high contents of As, pH and HCO3 −, a medium-high content EC, and low concentrations of NO3 −, SO4 2−, K +, and Cl − . The significant correlation between As and NO3 − indicates that NO3 − might be attributed to the use of phosphate fertilizers and a factor responsible for enhancing As in aquifers. The study also reports that the occurrence of high As and the presence of TMs in drinking water may be a result of local anthropogenic activities, such as irrigation, intensive land use and the application of agrochemicals. The insignificant correlation between As and SO4 2− demonstrated that As is released from SO4 2− minerals under reducing conditions. An elevated pH value along with decoupling of As and HCO3 − plays a vital role in mobilizing As to aquifer systems. Moreover, the positive relationship between As and Si indicated that As is transported in the biogeochemical environment. The reductive suspension of Mn(IV)-oxyhydroxides also accelerated the As mobilization process. Over exploitation of tube-well water and the competitive ion exchange process are also responsible for the release of As in aquifers. Highlights: Analyzed 82% drinking water contained As more than WHO recommended limit. Occurrence of other trace metals was within the safe limit. Ca-HCO3 -type drinking water was identified having high As, pH and HCO3 − . Intensive land use, agrochemicals usage and irrigation are responsible for high As. As is mobilized in biogeochemical and reduction environment with ion exchange process.